High-Performance Lithiated SiOX Anode Obtained by a Controllable and Efficient Prelithiation Strategy - Meng, Qinghai; Li, Ge; Yue, Junpei; Xu, Quan; Yin, Ya-Xia; Guo, Yu-Guo (ACS applied materials & interfaces, 2019)
Silicon-based electrodes are promising and appealing for futuristic Li-ion batteries because of its high theoretical specific capacity. However, massive volume change of silicon upon lithiation and delithiation, accompanied by continual formation and destruction of solid electrolyte interface (SEI) leads to low Coulombic efficiency. Prelithiation of Si-based anode is regarded as the effective way for compensating the loss of Li+ in the first discharging process. Here, a high-performance lithiated SiOx anode was prepared by using a controllable, efficient and novel prelithiation strategy. The lithiation of SiOx is homogeneous and efficient in bulk due to well-improved Li+ diffusion in SiOx. Moreover, the in-situ formed SEI during the process of prelithiation reduces the irreversible capacity loss in the first cycle, and thus improves the initial Coulombic efficiency (ICE). Half cells and full cells based on as-prepared lithiated SiOX anode prominently increase ICE from 79 to 89%, and 68 to 87%, respectively. It's worth mentioning that the homogeneously lithiated SiOx anode achieves stable 200 cycles in NCM622//SiOx coin full cells. These exciting results provide applicable prospects of lithiated SiOx anode in the next-generation high energy density Li-ion batteries.